Prostorski ETL za boljšo medopravilnost v GIS - Šušteršič, Katja (Geodetski vestnik, 2013)
dA spatial ETL tool that allows interoperability between spatial and non-spatial data is presented in this article. The primary goal of the tool is to provide spatial data processing and transformation among various data formats. This is made possible by the ETL process, which extracts, transforms and loads data. The use of spatial data has become significant in everyday life, because only correctly applying the data enables users to extract the true value spatial data offers. The main purpose of this article is to demonstrate the capability and usability of the spatial ETL tool, in order to introduce a more detailed definition of the ETL process to acquaint the reader with the FME Desktop tool, and to demonstrate the applicability of the tool in two case studies. In the first case, a unified spatial data warehouse is built from non-homogeneous data warehouses in order to assess the impacts and effects the geological basis had on the amount of damage to buildings in the 2004 earthquake. The second case demonstrates how the spatial ETL tool can be used to inform locals of predicted spatial changes in the area. The flexibility and the efficiency of the spatial ETL tool are successfully demonstrated in both cases; ETL turns out to be a robust tool for editing and analysing data.
Keywords: akcija COST; COST action; crowdsourcing; množični viri; prostorski podatki; prostovoljno množično zajemanje; VGI; voluntary spatial data